2020
DOI: 10.1262/jrd.2019-113
|View full text |Cite
|
Sign up to set email alerts
|

Expression of C–C motif chemokines and their receptors in bovine placentomes at spontaneous and induced parturition

Abstract: In bovine placentomes, the inflammatory response is considered important for the detachment of the fetal membrane from the caruncle after parturition. Glucocorticoids, a trigger of the onset of parturition, facilitate functional maturation of placentomes via prostaglandin (PG) and estrogen production in cattle. This study investigated how exogeneous glucocorticoids, which exert immunosuppressive effects, affect placental inflammation at parturition. Placentomes were collected immediately after spontaneous or i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…Although IFNT2-expressing cells in the caruncles were not identified in this study, we speculate that migrated macrophages from the maternal circulation into the caruncles might be a pivotal source of ligands that activate the IFN signaling pathway. This is consistent with our previous study showing that CD11B expression, a macrophage surface antigen, was increased in the caruncles during spontaneous parturition compared to induced parturition [ 21 ]. In addition, IFNA expression in this study, which is coordinately regulated with IFNT2 in PBL, did not increase in the placentomes during spontaneous parturition.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Although IFNT2-expressing cells in the caruncles were not identified in this study, we speculate that migrated macrophages from the maternal circulation into the caruncles might be a pivotal source of ligands that activate the IFN signaling pathway. This is consistent with our previous study showing that CD11B expression, a macrophage surface antigen, was increased in the caruncles during spontaneous parturition compared to induced parturition [ 21 ]. In addition, IFNA expression in this study, which is coordinately regulated with IFNT2 in PBL, did not increase in the placentomes during spontaneous parturition.…”
Section: Discussionsupporting
confidence: 93%
“…In this study, we revealed that enhanced glucocorticoid exposure in the TABET group normalized the expression of a substantial fraction of genes in the cotyledons. In contrast, this induction method did not upregulate CCL expression in the caruncles, suggesting that an inadequate inflammatory response may be an RFM factor in the TABET group [ 21 ]. Accordingly, the current study identified 774 DEGs in the caruncles of the TABET group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results on the maternal compartment of the bovine term placenta confirm the results from a previous study, asserted that during normal parturition, maternal macrophages are mostly pro‐inflammatory (Nelli et al., 2019). In a recent study (Hirayama et al., 2020), the mRNA expression of three inflammatory cytokines ( CCL2 , CCL5 , CCL8 ), two receptors ( CCR1 and CCR5 ) and a macrophage surface marker (CD11B) has been compared between cotyledon and caruncle tissues in spontaneously delivered foetal membranes. Interestingly, the expression of all six evaluated genes is higher in caruncular tissue compared to that of the cotyledon.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study (Hirayama et al, 2020), the mRNA expression of three inflammatory cytokines (CCL2, CCL5, CCL8), two receptors (CCR1 and CCR5) and a macrophage surface marker (CD11B) has been compared between cotyledon and caruncle tissues in spontaneously delivered foetal membranes. Interestingly, the expression of all six evaluated genes is higher in caruncular tissue compared to that of the cotyledon.…”
Section: Discussionmentioning
confidence: 99%